2005
DOI: 10.1007/bf02345966
|View full text |Cite
|
Sign up to set email alerts
|

Measuring orientation of human body segments using miniature gyroscopes and accelerometers

Abstract: In the medical field, there is a need for small ambulatory sensor systems for measuring the kinematics of body segments. Current methods for ambulatory measurement of body orientation have limited accuracy when the body moves. The aim of the paper was to develop and validate a method for accurate measurement of the orientation of human body segments using an inertial measurement unit (IMU). An IMU containing three single-axis accelerometers and three single-axis micromachined gyroscopes was assembled in a rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
390
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(403 citation statements)
references
References 37 publications
6
390
0
7
Order By: Relevance
“…Many studies have shown the validity of the IMC system for measurement of kinematics (Cutti et al, 2008;Faber et al, 2013b;Godwin et al, 2009;Luinge and Veltink, 2005;Plamondon et al, 2007;Roetenberg et al, 2005). However, the number of studies testing the validity of the system for the assessment of the kinetics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the validity of the IMC system for measurement of kinematics (Cutti et al, 2008;Faber et al, 2013b;Godwin et al, 2009;Luinge and Veltink, 2005;Plamondon et al, 2007;Roetenberg et al, 2005). However, the number of studies testing the validity of the system for the assessment of the kinetics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has some disadvantages including implementation complexity [39], [40], high sampling rate due to linear regression iteration (fundamental to the Kalman process) and the requirement to deal with large scale vectors to describe rotational kinematics in three-dimensions [38], [16]. There are some other alternatives to address these issues including Fuzzy processing [41] or frequency domain filters [42].…”
Section: B Sensor Orientation and Joint Angle Estimationmentioning
confidence: 99%
“…They exist in one-dimensional as well as multidirectional configurations and are similarly easy to apply as accelerometers. They are often used in combination with accelerometers, magnetic or other sensors and provide estimates for movement of segments in a kinematic chain (Brodie et al, 2008;Greene et al, 2010) using e.g., Kalman filter technique (Luinge & Veltink, 2005). A considerable advantage of this approach is that one can measure full body kinematics in virtually any environment (Cloete & Scheffer, 2010).…”
Section: Accelerometers and Gyroscopesmentioning
confidence: 99%